2018
DOI: 10.1149/2.0961810jes
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Ionic Current Limitations by Doping Graphite Anodes

Abstract: Density functional theory calculations were performed to study the impact of carbon site doping on akali metal intercalation behavior into graphite compounds. Substitutional boron doping was shown to effectively increase the intercalation potential of graphite versus both lithium and sodium metal anodes. The reduced graphite Fermi level of boron doped graphite was shifted away from the π * antibonding domain toward the more stable π bonds, hence lowering the reduction potential and improving the formation ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Li diffusion in graphene, graphite, and Si has been studied using density functional theory (DFT), a powerful tool for studying material properties. [301][302][303][304][305][306][307][308] Li diffusion behavior in Si/C composites has received limited study. Studies of amorphous Si-C layers have revealed that adding graphene substantially increases Li diffusivity near the Si/C interface.…”
Section: Diffusion Mechanism For Si/cmentioning
confidence: 99%
“…Li diffusion in graphene, graphite, and Si has been studied using density functional theory (DFT), a powerful tool for studying material properties. [301][302][303][304][305][306][307][308] Li diffusion behavior in Si/C composites has received limited study. Studies of amorphous Si-C layers have revealed that adding graphene substantially increases Li diffusivity near the Si/C interface.…”
Section: Diffusion Mechanism For Si/cmentioning
confidence: 99%
“…A thermodynamic modification was also used to enhance AMI intercalation in graphite, and this was achieved by using carbon site doping such as doping with boron. 91 When used as a stable carrier for alloy-conversion type electrodes, graphite is reported to have shown an increased capacity in such batteries. 23,27,[92][93][94][95][96] The FeCl 3 -GIC electrode demonstrated high reversible capacity and a long cyclic performance due to the expanded channels for ion transport and the additional reaction of FeCl 3 .…”
Section: Graphite Intercalation Compounds For Dual Ion Batteriesmentioning
confidence: 99%
“…The first-principles theory provides a powerful tool for investigating material properties via atomistic-scale simulation. 30−32 A considerable number of studies using density functional theory (DFT) within the firstprinciples theory frame have been reported on Li diffusion in Si (crystalline/amorphous bulk Si 33,34 and Si nanowires 35,36 ), graphite, 37,38 and graphene. 39,40 interfacial behavior during lithiation.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies have well-described the electrochemical performance of such Si/C composite materials at the cell or electrode level. Nevertheless, it is challenging to use experimental methodologies to explore the lithiation mechanism at the atomistic scale, which is significant for anode material design and improvement. The first-principles theory provides a powerful tool for investigating material properties via atomistic-scale simulation. A considerable number of studies using density functional theory (DFT) within the first-principles theory frame have been reported on Li diffusion in Si (crystalline/amorphous bulk Si , and Si nanowires , ), graphite, , and graphene. , However, until recently, little work has been devoted to Li diffusion behavior in Si/C composites. First, investigators have examined the effects of graphene material on Li diffusion in Si by focusing on the Si/C interfacial behavior during lithiation .…”
Section: Introductionmentioning
confidence: 99%